Field-emission-assisted approach to dry micro-electro-discharge machining of carbon-nanotube forests - Saleh, Tanveer; Dahmardeh, Masoud (American Institute of Physics, 2011)
This work investigates dry micro-electro-discharge machining (lEDM) of vertically aligned carbon nanotube (CNT) forests that are used as cathodes in the process, as opposed to conventional lEDM where the material to be machined forms the anode, toward achieving higher precision in the patterned microstructures. The new configuration with the reversed polarity is observed to generate higher discharge currents in the process, presumably due to effective field-emission from CNTs. This effect allows the process to be performed at very low discharge energies, approximately 80smaller than in the conventional normal-polarity case, with the machining voltage and tolerance down to 10V and 2.5 lm, respectively, enabling high-precision high-aspect-ratio micropatterning in the forests. The new approach is also demonstrated to make the process faster, cleaner, and more stable than conventional processing. Spectroscopic analyses of the forests processed by reverse lEDM show no evidence of significant crystalline deterioration or contamination in the CNTs.